2018
DOI: 10.1002/chem.201705619
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Synthetically Versatile Pyridylidene Amide Ligands for Efficient Iridium‐Catalyzed Water Oxidation

Abstract: The synthetic versatility of pyridylidene amide (PYA) ligands has been exploited to prepare and evaluate a diverging series of iridium complexes containing C,N-bidentate chelating aryl-PYA ligands for water oxidation catalysis. The phenyl-PYA lead structure 1 was modified (i) electronically through introduction of one, two, or three electron-donating methoxy substituents on the aryl ring, (ii) by incorporating long aliphatic chains to the pyridyl fragment of the PYA unit, and (iii) by altering the PYA position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 83 publications
(75 reference statements)
2
46
0
Order By: Relevance
“…Very recently, they investigated the promoting effect of incorporating MeO-groups. 188,189 Macchioni and co-workers found that the simple Cp*Ir complex [Ir(Cp*)(H 2 O) 3 ] 2+ (30) showed faster catalysis than those bearing auxiliary chelating ligands. 190 Hetterscheid and Reek reported a series of NHC-ligand-coordinated half-sandwich Cp*Ir complexes (31) with both high TOF (1.5 s À1 ) and high TON (42000) by using Ce 4+ as the oxidant.…”
Section: Overview Of Molecular Water-oxidation Catalysts (Wocs)mentioning
confidence: 99%
“…Very recently, they investigated the promoting effect of incorporating MeO-groups. 188,189 Macchioni and co-workers found that the simple Cp*Ir complex [Ir(Cp*)(H 2 O) 3 ] 2+ (30) showed faster catalysis than those bearing auxiliary chelating ligands. 190 Hetterscheid and Reek reported a series of NHC-ligand-coordinated half-sandwich Cp*Ir complexes (31) with both high TOF (1.5 s À1 ) and high TON (42000) by using Ce 4+ as the oxidant.…”
Section: Overview Of Molecular Water-oxidation Catalysts (Wocs)mentioning
confidence: 99%
“…[44][45][46] The flexibility imparts catalytic activity, and is further modulated upon alteration of the pyridine substitution pattern from para-PYAs (A, B) to meta-PYA scaffolds (C, Scheme 1). 47 Of note, such meta-PYA ligands cannot be represented by a neutral resonance structure and feature only zwitterionic structures. 48 Provided resonance structures D-F are also relevant, then these ligands are mesoionic N-donor systems, 49 related to mesoionic N-heterocyclic carbenes.…”
Section: Introductionmentioning
confidence: 99%
“…Successively, many other molecular Ir WOCs were reported, and many excellent and exhaustive reviews recently appeared in the literature , , . Herein, the focus is on the stability and activity of Ir WOCs, two strictly interlocked and crucial aspects.…”
Section: Molecular Ir Wocsmentioning
confidence: 99%